Translating religion: what is lost and gained? - Tietz, Christiane; DeJonge, Michael P. (Routledge studies in religion, 2015)
Cover -- Title -- Copyright -- Contents -- List of Figures -- Preface -- Introduction: Translating Religion -- 1 Translating Dao: Cross-Cultural Translation as a Hermeneutic of Edification -- 2 Historical Translation: Pseudo-Dionysius, Thomas Aquinas, and the Unknown God -- 3 Philological Limits of Translating Religion: Śraddhā and Dharma in Hindu Texts -- 4 Translating Religion between Parents and Children -- 5 Thick Translation of Religion between Cultures: The Basel Mission in Ghana -- 6 Habermas's Call for Translating Religion into Secular Language -- 7 Does Allah Translate 'God'? Translating Concepts between Religions -- 8 Translating Religious Symbol Systems: Some Preliminary Remarks on Christian Art in China -- Conclusion: What is Lost and Gained? -- Contributors -- Index.